A Work and Learning Dual System Model for Talent Development in South Korea: A Multiple Stakeholder View. Issue 4 (November 2018) - Chai, Dae Seok; Kim, Sehoon; Kim, Minjung
The Problem: Although a continual nationwide drive to develop human resources has enabled Korea to achieve rapid economic growth, Korean society has recently faced several emerging social and economic issues at the national, organizational, and individual levels including a higher unemployment rate, a competency mismatch between the skills new employees possess and what employers require, and the required additional cost of reeducation. To address these issues, the Korean government and private organizations have cooperated to create a new government-private sector collaboration model called a work and learning dual system (WLDS). The Solution: Our study explored how WLDS functions in the workplace and its influence on learning and performance outcomes at various levels through interviews with multiple stakeholders and documents collected from the organizations responsible for the implementation of WLDS. Twelve employees in the organizations were interviewed, and internal and external documents were analyzed. The findings were presented within the key dimensions of talent development by Garavan, Carbery, and Rock, and the outcomes were specified from multiple stakeholders at various levels. WLDS provides important implications for research on not only talent development but also human resource development (HRD) practices through public–private partnerships. The Stakeholders: The findings offer several important practical insights for multiple stakeholders. HRD practitioners and policy makers in emerging markets can learn from this type of combined talent development program with structured off- and on-the-job-training. In terms of national HRD, they can strategically and systematically improve their talent development programs and cooperate with relevant governmental agencies.